The relationship between executive functions and sports experience, relative age effect, as well as physical maturity in youth soccer players of different ages - Heilmann, F.; Memmert, D.; Weinberg, H.; Lautenbach, F. (International Journal of Sport and Exercise Psychology, 2023)
Sports psychology and kinesiology research focused on executive functions in the last ten years as cognitive functions could be one of the smallest adjustments possible in high-level athletes. We examined the connection of sports experience, (relative-) age effects, and physical maturity on the executive functions in male youth soccer players (N = 110). Working memory was assessed using the 3-back task, inhibition was measured using the flanker task, and cognitive flexibility was measured using the number-letter task. We hypothesised that sports experience, (relative-) age effects and physical maturity are positively correlated with executive functions. However, the linear regression model MANOVA test statistics revealed only an impact of calendar age on executive functions. The results demonstrate that athletes attain a certain level in executive functions and gain specific cognitive skills in their sports. Nevertheless, questions about the transfer of executive functions on sport-specific cognitive skills remain unclear.